Case Report: Innate Immune System Challenge Unleashes Paraneoplastic Neurological Autoimmunity - Zhu, Mingqin; Ma, Yuetao; Zekeridou, Anastasia; Lennon, Vanda A. (Frontiers in Neurology, 2020)
Paraneoplastic autoimmune neurological disorders reflect tumor-initiated immune responses against onconeural antigens. Symptoms and signs can affect the central and/or peripheral nervous systems, neuromuscular junction or muscle, and typically evolve subacutely before an underlying neoplasm is discovered. We describe four patients whose neurological symptoms were precipitated by potent innate immune system challenges: bladder instillation of BCG, tick bite and an “alternative cancer therapy” with bacterial extracts and TNF-α. We hypothesize that a tumor-initiated autoimmune response (evidenced by autoantibody profiles), pre-dating the immune system challenge, was unmasked or amplified in these patients by cytokines released systemically from innate immune cells activated by microbial pathogen-associated molecular patterns (PAMPs). The resultant upregulation of cognate onconeural peptides as MHC1 protein complexes on neural cell surfaces would render those cells susceptible to killing by CD8+ T cells, thus precipitating the patient's neurological symptoms.